Synthesis and properties of partially biodegradable fluorinated polyacrylate: Poly(l‑lactide)‑co‑poly(hexafluorobutyl acrylate) copolymer. (15th January 2019) - Huang, Yun; Pan, Yonghao; Wang, Weiwei; Jiang, Long; Dan, Yi
Abstract: In order to alleviate the environmental pollution from fluoropolymer, the biodegradable poly( l ‑lactide) (PLLA) segments were introduced into fluorinated polyacrylate. The PLLA macromonomers with vinyl terminal group and different molecular weight, i.e. 2500, 7400 and 14, 700, were synthesized by ring opening polymerization of l ‑lactide (LLA) first, then copolymerized with hexafluorobutyl acrylate (HFBA) through free radical copolymerization. By changing the macromonomers and feeding ratio of the macromonomer and HFBA, the poly( l ‑lactide)‑ co ‑poly(hexafluorobutyl acrylate) (PLLA- co -PHFBA) copolymers with different structures were obtained. Structures of the PLLA macromonomers and the copolymers were confirmed by FTIR, 1 H NMR and GPC. The crystallization, thermal decomposition resistance, surface hydrophobicity and hydrolytic degradation were also investigated. The results show that the PLLA segments in the copolymers still have the crystallization capacity and the highest crystallinity reaches 36%. PLLA- co -PHFBA-4 with the longest PLLA segments has the highest initial decomposing temperature up to 355 °C. The hydrophobicity of the copolymers is mainly related to the content of PHFBA segments. The length of PLLA segments also have some effect on the hydrophobicity. An obvious mass loss of the copolymers was observed in 35 days under the hydrolytic degradation and it was related to PHFBA content and PLLA segment's length, exhibiting partially biodegradable behavior. Graphical abstract: Highlights: Vinyl group capped poly( L -lactide) macromonomer with different molecular weight was designed and synthesized sucessfully. Biodegradable poly( L -lactide) segments were introduced to fluorinated polyacrylate. The hydrophobicity of poly( L -lactide)-co-poly(hexafluorobutyl acrylate) copolymers is related to the fluorinated component. The mass loss reached 2~5 wt% of the studied copolymers under only 35 days' hydrolytic degradation.